Structural Assessment of Lead Free Solder Joint of Miniaturized Electronics Assembly - Saad, Abdullah Aziz; Bachok, Zuraihana; Che Ani, Fakhrozi; Jalar, Azman; Abas, Mohamad Aizat (International Journal of Integrated Engineering, 2018)
This paper presents a study on structural assessment of ultra-fine package assembly with nano-composites lead free solder joint after reflow soldering process. In this work, various nanoparticles (i.e. TiO2, Fe2O3 and NiO) with different weightage percentage (i.e., 0.01, 0.05 and 0.15 wt.%) were successfully incorporated into SAC305 solder paste using the mechanical solder paste mixer to synthesize novel lead-free composite solders. Effects of the nanoparticles addition on the quality of joining and fillet height between various weightage (wt.%) for the ultra-fine package assembly in the reflow soldering process have been investigated after the reflow soldering process by using the scanning electron microscope (SEM) system equipped with an energy dispersive X-ray spectroscopy (EDS) and XTV 160 x-ray inspection system. The experimental results show the increment of TiO2, Fe2O3 and NiO nanoparticles addition to 0.15wt.%, 0.05wt.% and 0.01wt.%, respectively, produce highest fillet height of each composition of nanoparticles solder paste. Among all these new composition of nanoparticles solder paste, NiO nanoparticles reinforced solder paste with 0.01wt.% yielded highest fillet height The miniaturized solder joints do not cause any problem in terms of solder voids. The findings show the capability of the reflow soldering process in assembling miniaturized electronics assembly and expected to provide a reference in electronic package industry.